1991
DOI: 10.1139/z91-282
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific patterns of synthesis of heat-shock proteins and thermal tolerance of the fathead minnow (Pimephales promelas)

Abstract: 1991. Tissue-specific patterns of synthesis of heat-shock proteins and thermal tolerance of the fathead minnow (Pimephales promelas). Can. J. Zool. 69: 2021-2027. Qualitative and quantitative differences in the heat-shock response in brain, gill, and striated muscle tissues of the fathead minnow (Pimephales promelas) were investigated. The maximum sublethal heat-shock temperature was 34°C. The heat-shock proteins (hsps) induced, their biosynthetic rates, minimum temperatures required for induction, and maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 21 publications
6
31
2
Order By: Relevance
“…This is in contrast to previous studies showing heat-shock-induced increases in Hsp70 levels in brain tissue of other fishes, including killifish (Koban et al, 1991), fathead minnow (Dyer et al, 1991), buffalo sculpin (Enophrys bison), speckled sanddab (Citharichthys stigmaeus), and English sole (Parophrys vetulus) (Dietz and Somero, 1993). Similar to our previous studies on green sturgeon fingerlings , there was a high degree of variability in brain Hsc/Hsp70 levels of the most feed restricted green and white sturgeon, regardless of temperature.…”
Section: Hsc/hsp70 Protein Levelscontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to previous studies showing heat-shock-induced increases in Hsp70 levels in brain tissue of other fishes, including killifish (Koban et al, 1991), fathead minnow (Dyer et al, 1991), buffalo sculpin (Enophrys bison), speckled sanddab (Citharichthys stigmaeus), and English sole (Parophrys vetulus) (Dietz and Somero, 1993). Similar to our previous studies on green sturgeon fingerlings , there was a high degree of variability in brain Hsc/Hsp70 levels of the most feed restricted green and white sturgeon, regardless of temperature.…”
Section: Hsc/hsp70 Protein Levelscontrasting
confidence: 99%
“…Highly induced Hsp70 levels in response to heat shock in the same tissues have also been reported in other fishes (e.g., fathead minnow, Pimephales promelas (Dyer et al, 1991); mummichog, Fundulus heteroclitus (Koban et al, 1991)). The discrepancy in Hsp70 responses to increased temperature between the current study and Wang et al Fig.…”
Section: Hsc/hsp70 Protein Levelssupporting
confidence: 61%
“…The tissue-specific differences in hsp60 expression found in this study are similar to those observed for hsp70 expression in carp, Cyprinus carpio L. 1758 (Wang et al, 2007). Similarly, tissue-specific hsp70 expression was reported in the killifish Fundulus heteroclitus (L. 1766) (Koban et al, 1991), fathead minnow Pimephales promelas Rafinesque 1820 (Dyer et al, 1991), brown trout Salmo trutta L. 1758 (Schmidt et al, 1998), and sea lamprey Petromyzon marinus L. 1758 (Wood et al, 1999). The fact that stress responses differ between tissues supports the hypothesis that the thermal limits of an organism are governed by certain tissues more than others (Dyer et al, 1991).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, tissue-specific hsp70 expression was reported in the killifish Fundulus heteroclitus (L. 1766) (Koban et al, 1991), fathead minnow Pimephales promelas Rafinesque 1820 (Dyer et al, 1991), brown trout Salmo trutta L. 1758 (Schmidt et al, 1998), and sea lamprey Petromyzon marinus L. 1758 (Wood et al, 1999). The fact that stress responses differ between tissues supports the hypothesis that the thermal limits of an organism are governed by certain tissues more than others (Dyer et al, 1991). In this study, a prominent induction of hsp60 synthesis was clearly apparent in the liver.…”
Section: Discussionmentioning
confidence: 67%
“…Many different factors, like temperature (Dyer et al 1990), metals (Levinson et al 1980), hypoxia (Sciandra et al 1984), and osmolarity (SheikhHamad et al 1994) can induce perturbations in the physico-chemical environment, becoming stressors for animals living in that environment. Fish are constantly exposed to stressful conditions, and as a consequence have evolved different stress response systems, which have been expressed at all levels of biological organization.…”
Section: Introductionmentioning
confidence: 99%